(untitled) (Universal International Scientific Journal, 2026)
This article is aimed at analyzing educational problems that may arise during the introduction of digital technologies in the modern education system. Our study examines the impact of digital transformation on the efficiency of the education system, its shortcomings, and pedagogical mechanisms aimed at preventing them.